2019
DOI: 10.1002/advs.201900547
|View full text |Cite
|
Sign up to set email alerts
|

Ammoniating Covalent Organic Framework (COF) for High‐Performance and Selective Extraction of Toxic and Radioactive Uranium Ions

Abstract: An ideal porous adsorbent toward uranium with not only large adsorption capacity and high selectivity but also broad applicability even under rigorous conditions is highly desirable but still extremely scarce. In this work, a porous adsorbent, namely [NH 4 ] + [COF‐SO 3 − ], prepared by ammoniating a SO 3 H‐decorated covalent organic framework (COF) enables remarkable performance for uranium extraction. Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(83 citation statements)
references
References 48 publications
0
83
0
Order By: Relevance
“…It is worth noting that TFPT-BTAN-AO can achieve a saturation capacity of about 98% within 45 min. This is in sharp contrast to the long contact times required for other uranium sorbent materials, which typically range from hours to days 7,[47][48][49] . For comparison, POP-TB-AO took 85 min to reach 95% of its equilibrium adsorption capacity.…”
Section: B L a N K C O 2 + C A 2 + C D 2 + C R 3 + S R 2 + M N 2 + F mentioning
confidence: 88%
“…It is worth noting that TFPT-BTAN-AO can achieve a saturation capacity of about 98% within 45 min. This is in sharp contrast to the long contact times required for other uranium sorbent materials, which typically range from hours to days 7,[47][48][49] . For comparison, POP-TB-AO took 85 min to reach 95% of its equilibrium adsorption capacity.…”
Section: B L a N K C O 2 + C A 2 + C D 2 + C R 3 + S R 2 + M N 2 + F mentioning
confidence: 88%
“…6 Owing to economics and versatility, chemical adsorption is considered to be the most promising technology for extracting uranium from seawater. 7,8 Recently, numerous porous materials have been developed for uranium extraction, [9][10][11][12][13] such as porous aromatic frameworks (PAFs), 14,15 metal-organic frameworks (MOFs), 6,16 and porous organic polymers (POPs); 17 all of them exhibit impressive uranium extraction performance. However, most adsorbents have poor stability in complex marine environments, leading to decomposition during long-term immersion in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…This composite also features better selectivity among 10 coexisting ions (Zn 2+ , Co 2+ , Ni 2+ , Mn 2+ , Sm 3+ , Gd 3+ , La 3+ , Nd 3+ , Sr 2+ , and Ce 3+ ) and excellent acid stability after the treatment of 8 M HNO 3 for 12 h. Recently, Xiong et al. 82 synthesized COF-SO 3 H with a combination of 2,4,6-triformylphloroglucinol and 1,2-dichlorobenzene, and then prepared [NH 4 ] + [COF-SO 3 − ] by immersing COF-SO 3 H in NH 3 ·H 2 O. The abundant –SO 3 − units in the pore wall could implement the coordination interaction toward U(VI).…”
Section: Removal Of Radionuclides By Cof-based Materialsmentioning
confidence: 95%
“…The highest adsorption capacity for U(VI) has been reported to be 851 mg·g −1 for [NH 4 ] + [COF-SO 3 − ]. 82 To the authors’ knowledge, the most selective COF-based adsorbent for U(VI) reported to date is o -GS-COF. 81 The COF with the highest radiation stability reported is SCU-COF-1, which has been confirmed to maintain its physicochemical property even under irradiation of 600 kGy β-rays and 600 kGy γ-rays, 217 enough to meet the need of applications in radioactive waste management.…”
Section: Removal Of Radionuclides By Cof-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation